2011
DOI: 10.1097/mpg.0b013e3182182ff8
|View full text |Cite
|
Sign up to set email alerts
|

Siglec‐F Inhibition Reduces Esophageal Eosinophilia and Angiogenesis in a Mouse Model of Eosinophilic Esophagitis

Abstract: Objectives Eosinophilic esophagitis (EoE) is a disorder characterized histologically by tissue eosinophilia. Sialic acid–binding immunoglobulin-like lectin (Siglec-F) is a receptor highly expressed on mouse eosinophils and mediates eosinophilic apoptosis. We investigated whether administration of an anti-Siglec-F Ab would reduce esophageal eosinophilic inflammation and remodeling in a mouse model of egg ovalbumin (OVA)–induced EoE. Subjects and Methods Three groups of mice were studied (no OVA, OVA + anti-Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
78
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(81 citation statements)
references
References 28 publications
2
78
0
1
Order By: Relevance
“…Siglecs are expressed by a number of immune cells, including eosinophils, and Siglecs are involved in regulating inflammation. Rubenstein et al (133) demonstrated that anti-Siglec-F antibody decreased eosinophil infiltration, angiogenesis, fibronectin deposition, and basal zone hyperplasia in a mouse model of EoE. These findings suggest that Siglec-8, the human paralog of Siglec-F, might be a therapeutic target for improving tissue remodeling in patients with EoE.…”
Section: Eoe Therapies and Remodelingmentioning
confidence: 87%
See 1 more Smart Citation
“…Siglecs are expressed by a number of immune cells, including eosinophils, and Siglecs are involved in regulating inflammation. Rubenstein et al (133) demonstrated that anti-Siglec-F antibody decreased eosinophil infiltration, angiogenesis, fibronectin deposition, and basal zone hyperplasia in a mouse model of EoE. These findings suggest that Siglec-8, the human paralog of Siglec-F, might be a therapeutic target for improving tissue remodeling in patients with EoE.…”
Section: Eoe Therapies and Remodelingmentioning
confidence: 87%
“…The ovalbumin-challenged mouse model does not involve genetic manipulations. Rather, BALB/c mice are sensitized to ovalbumin by intraperitoneal administration of the egg allergen, followed by the chronic intraesophageal administration of ovalbumin (133). These animals also develop esophageal eosinophilia and remodeling.…”
Section: Eoe Therapies and Remodelingmentioning
confidence: 96%
“…Oesophageal studies in the mouse have bifurcated based on the experimental strategies utilised to generate these models of EoE: (1) Sensitisation/local challenge approaches in which wild-type mice undergo a primary sensitisation event to allergen (and/or a contact irritant) followed by a secondary topical challenge of the oesophagus with the same agent 3 6 7. (2) Transgenic overexpression in mice of candidate inflammatory genes identified from clinical studies of EoE patients 5 37.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of eosinophil depletion on allergic inflammatory diseases has been explored most directly in mouse models using antibodies to Siglec-F, which effectively deplete eosinophils from blood and tissues 122 . Using this approach, depletion of eosinophils has been documented to significantly reduce pathology in models of allergic rhinitis 123 , esophageal eosinophilia 124 , and allergen induced eosinophil airway remodeling 125 . A similar approach has been used to demonstrate a beneficial effect of eosinophil depletion on allergen induced intestinal inflammation 125 .…”
Section: Siglecs As Therapeutic Targetsmentioning
confidence: 99%